The Influence Of Internship Experience And Work Interest On The Job Readiness Of Students Of The Faculty Of Economics And Business, Udayana University - Ni Wayan Sonia Ari Fatni; I Gusti Bagus Honor Satrya (Jurnal Syntax Transformation, 2023)
The work readiness of students in the Faculty of Economics and Business, Udayana University before entering the workforce is crucial to be known. This is because after completing their studies, most students will face a higher level of life than before, which is working. Students who are willing to enter the workforce will realize that working is not an easy matter, so it needs to be balanced with good preparation. Students can improve their work readiness by participating in various internship programs that are in line with their job interests. Therefore, through this phenomenon, the researcher is interested in conducting research aimed at determining the influence of internship experience and job interest on the work readiness of students in the Faculty of Economics and Business, Udayana University. The data analysis of this research uses multiple linear regression analysis method with the help of SPSS Statistics 25. To collect data, this research uses a questionnaire addressed to students in the Faculty of Economics and Business, Udayana University, batch of 2019, with a total of 89 respondents. The results of this study show that internship experience and job interest have a positive and significant influence on the work readiness of students in the Faculty of Economics and Business, Udayana University.